Analysis of conceded goals of HC Slovan Bratislava in seasons 2012-2013 to 2014-2015 in the continental hockey league - Opáth, L.; Pupiš, M.; Beták, B.; Rybár, P.; Pavlovic, R. (Sport Science - International Scientific Journal of Kinesiology, 2020)
The aim of the research was analysis of conceded goals of HC Slovan Bratislava in seasons 2012-2013 to 2014-2015 in The Continental Hockey League (KHL) from the viewpoint of place into which the goalkeepers were conceded goals. Studied group involved 3 goalkeepers. The research was carried out by means of direct observation. Conceded goals were divided into 9 categories. From the viewpoint of place into which the goalkeepers were conceded goals the authors have found out, that the goalkeeper got 26% of empty net goals. Goalkeeper 2 got 32% of goals over the catch glove, which he wears on his left hand. Goalkeeper 3, similarly like Goalkeeper 1, the most often got empty net goals and thus 37% of the total conceded goals. In practice we recommend to do the statistics of places, into which goalkeepers the most often get the goals and based on their evaluation to focus the training process on particular weaknesses of goalkeeper or weaknesses of defensive activities of team.